#14 Rapid, Non-Invasive Detection of Non-H. pylori Helicobacter Infections in Immunocompromised Children Using Microbial Cell-Free DNA Next Generation Sequencing in Plasma. (14th June 2022) - Berman, David M
Abstract: Background: Non-H. pylori Helicobacter (NHPH) infections are more common in immunocompromised hosts and are associated with chronic infection in patients with X-linked agammaglobulinemia. Enterohepatic Helicobacter spp. cause systemic disease including cellulitis, bacteremia, endocarditis, meningitis, arthritis, hepatobiliary disease, and enteritis. NHPH are fastidious gram-negative organisms and are rarely detected by culture or nucleic acid amplification tests in clinical laboratories, resulting in potentially poor clinical detection and treatment. We present data demonstrating the diagnostic advantage of using plasma microbial cell-free DNA Sequencing to rapidly identify NHPH to the species level. Method: The Karius TestTM (KT) was developed and validated in Karius's CLIA certified/CAP accredited lab (Redwood City, CA) and detects mcfDNA in plasma. Following DNA extraction, next-generation sequencing (NGS) is performed, and sequences are aligned to a curated database of > 1000 organisms. Microorganisms observed above background at statistically significant levels are reported and quantified in molecules per microliter (MPM). We conducted a retrospective review of KT detections of NHPH from December 2016-November 2021. A subset of pediatric patients (age <=21 years) was identified from this cohort. Available clinical information was extracted from the test requisition form. Results: KT detected NHPH in 23 patients among 11 unique institutions in the span of 5 years, including 10 (43%) pediatric patients (Table 1). Nine of ten detections were quantified (Median 110 MPM; range 48-20932, MPM). The reference interval of mcfDNA abundance for all NHPH species (defined by the 97.5th %ile) in a cohort of 684 healthy subjects is 0 MPM (for comparison the reference interval for H. pylori is 42.2 MPM). The highest detection was H. magdeburgensis 20, 932 MPM. Of the 10 patients, 8 were male and 2 were female and the mean age was 10.5 years (range 3-17). Nine of 10 patients had information regarding underlying diagnosis. There were 6 patients with primary immunodeficiency including 5 with X-linked agammaglobulinemia with a diverse manifestation of infections. Two patients had serial testing during the intercurrent infectious episode to monitor the response to treatment. Serial testing in one patient showed a dramatic decrease of NHPH mcfDNA from 27, 907 MPM to 1, 079 MPM over a 6-day span. Serial testing in a second patient showed a decrease of the NHPH mcfDNA from 124 MPM to an undetectable range 14 days later. Conclusion: These cases highlight the potential use of rapid, non-invasive, plasma mcfDNA to diagnose and potentially monitor the response to treatment of infections caused by NHPH, especially in patients with primary immunodeficiency. NHPH are difficult to detect and identify using conventional microbiological methods and plasma mcfDNA NGS may play an important role in detecting these fastidious microorganisms and serial testing.